An interactive VR platform with emotion recognition for self-attachment intervention - Polydorou, Neophytos; Edalat, Abbas (EAI Endorsed Transactions on Pervasive Health and Technology, 2021)
INTRODUCTION: Self-attachment is a new self-administrable psychotherapeutic intervention based on creating an affectional bond between the user and their childhood-self using their childhood photos to develop the capacity for affect self-regulation. Technological advances, such as virtual reality (VR), can enhance the procedure of this intervention and make it scalable. METHODS: We have developed a user-friendly, interactive VR platform for self-attachment featuring a virtual assistant and a customised child avatar that resembles the user in their childhood. The virtual agent interacts with the user and using an emotion recognition algorithm can provide suggestions for the user to undertake an appropriate self-attachment sub-protocol. Furthermore, the platform allows user interaction with the child avatar, such as embracing the avatar. RESULTS: We show by a small preliminary trial that such a VR experience can be realistic, leading to a positive emotion change in the user.